SURVEI STRATEGI MENULIS KALIMAT MAHASISWA SEMESTER II PENDIDIKAN BAHASA INGGRIS UNIVERSITAS MUHAMMADIYAH PURWOKERTO - Dyah Kusumastuti; Listiani Listiani (Kajian Linguistik dan Sastra, 2020)
This research was aimed to describe the writing strategy of the second semester students of University Muhammadiyah of Purwokerto in the academic year 2015/2016. The method was qualitative descriptive. There were 57 students of the second semester  students as the subject of the research. However, the data collection was collected through questionaire. The result was likely about the percentage from the questionaire. In preparation step, 49% respondents admitted that they use cognitive strategy, they looked for the information they wanted to write and also collected some vocabularies before writing. In the second item, there were 60% respondents who have social strategy. Therefore, if they have problem in their writing, they will ask their friends. Cognitive strategy is also used by 67% respondents, it happened when the students said that grammar was the part from their writing in which it was the most often to be corrected. Moreover, cognitive strategy again was used by 84% and 54% when they did not know about grammar and word from their writing, they would open grammar book and dictionary. The last, there were 46% respondents had cognitive and social strategy, that was about to use internet or social media as the additional source outside class.    Keywords: writing strategy, cognitive, metacognitive, social